Analisis Peran Keluarga Bapak Yanto dalam Meningkatkan Kemampuan Bahasa Pada Anak - Diana Pratiwi; Siska Sri Lestari; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to describe the efforts and methods used by Mr. Yanto's family to improve children's language skills. This study uses a qualitative approach and analytic descriptive method. Data collection techniques using techniquesobservation, observation techniques, interview techniques, and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions or verification. The results of the analysis show that there are several efforts made by Mr. Yanto's family in improving children's language skills. The first thing to do is start from an early age, namely by teaching greetings or learning to greet people. Mr. Yanto's two families taughthis son to use polite speech when asking for help is required to say the word"help", get gifts or praise from other people say"Thank You" ,then if you make a mistake, no matter how big or small the mistake, you must apologize by saying"sorry",then if passing people have to say"Excuse me".The third is by inviting children to talk, chatting when they are together or by introducing something new. Something around it. While the method used by Mr. Yanto's family in improving children's language skills is through the maxim of wisdom, the maxim of generosity, the maxim of appreciation, and the maxim ofsympathy.